Alignment of The Concept of Mohammad Hatta Cooperative and Sharia Cooperative to Prevent Inflation - Peti Savitri (Journal of Economicate Studies, 2020)
This article raises the concept of the cooperative "Bung Hatta" which is harmonized with the principles of Islamic cooperatives as a discourse that might be one of the models of inflation control policies in Muslim countries. Through the study of literature, the concept is presented descriptively to explain how cooperatives can become a powerful driver of the people's economy so that ultimately it becomes a solution not only to the problem of inflation that always arises in all countries, especially developing countries, but also can be a solution to the main Macroeconomic problems other than inflation, namely economic growth and unemployment.